The Effect of Osteocalcin in Middle-Age Women With and Without Type2 Diabetes Mellitus - Hadeer I. Jassim; Ammar L. Hussein (Diyala Journal of Medicine)
Background: Diabetes mellitus is a chronic disease that affects people of all ages. It's caused by deficiencies in insulin action and secretion, leading to long-term hyperglycemia. This can harm key organs such as the kidneys, heart, eyes, nerves, and blood vessels. Managing diabetes requires significant lifestyle changes and can impact both the patient and their family. Small and bone-specific, osteocalcin (OCN) is a non-collagen protein that is mostly present in bone. It is a sensitive marker of bone formation and primarily attaches to the extracellular matrix of bone after being carboxylated. Small amounts of OCN are also released into the bloodstream, where it aids in glucose and fat metabolism.